Electric power systems load forecasting: A survey - Lotufo, D. P. [UNESP]; Minussi, C. R. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 1999)
This work reviews the latest works on load forecasting, classifying them according to presented methods and models, as statistical, intelligent systems, neural networks and fuzzy logic. As there are many different models and methods, we have studied the principal ones since those considered as classical statistical until those modern like neural networks and fuzzy logic. We emphasize the importance of load forecasting in modern operation centers, and conclude that nowadays the most used forecasting methods are the neural networks and fuzzy logic, but the statistical ones continue being used although in less quantity.
Keywords: Fuzzy logic; Intelligent systems; Load forecasting; Load models; Neural networks; Prediction methods